The effects of official English laws on limited-English-proficient workers - Madeline Zavodny (Federal Reserve Bank of Atlanta, 1998)
Workers with limited English skills may suffer adverse effects in the labor market when states declare English the official language. If employers view official English laws as allowing or requiring them to adopt workplace English-only rules that lower the demand for limited-English-proficient workers, such laws may harm individuals who do not speak English very well. Using data from the 1980 and 1990 Census, I estimate whether the earnings and other labor market outcomes of workers who have limited English proficiency and live in states that adopted official English laws declined relative to other workers'. The results suggest a substantial decline in the annual earnings of men with limited English proficiency.
Keywords: 330; Discrimination in employment; Public policy